Heaven's kitchen: living religion at God's Love We Deliver - Bender, Courtney (Morality and society series, 2003)
For over a year Courtney Bender worked as a volunteer for a nonprofit, nonreligious organization, helping to prepare home-cooked meals for people with AIDS. Paying close attention to what was said and not said, Bender traces how the volunteers gave voice to their moral positions and religious values. She also examines how they invested their conversations, and mundane activities such as cooking, with personal meaning that in turn affected how they saw their own spiritual lives. 'Heaven's Kitchen' shows faith as a living practice, reshaping our understanding of the role of religion in contemporary American life